Water security status and associated challenges in Guwahati city (India) - Бхараті Хазаріка; Бімал К. Кар (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія)
Introduction. Although cities are becoming increasingly developed in all spheres, there occur formidable multidimensional challenges associated with urban development. One such challenge is the water security, as water in the urban areas is the hotspot in regard to its consumption due to fast growing population on small geographical extent. Moreover, the development of urban water system is unable to keep pace with the rapid growth of population in cities, leaving majority of the dwellers lacking access to water supply system.